Interactions between rodents and weeds in a lowland rice agro‐ecosystem: the need for an integrated approach to management - Htwe, Nyo Me; Singleton, Grant R.; Johnson, David E. (Wiley, 2019)
Rodents and weeds are important pests to rice crops in Southeast Asia. The interaction between these 2 major pests is poorly documented. In temperate cereal systems, seeds of grass weeds can be an important food source for rodents and weed cover along crop margins provides important refuge for rodents. In 2012 and 2013, a replicated study (n = 4) in Bago, Myanmar compared 4 treatments (rodents and weeds; no rodents and weeds; rodents and no weeds; no rodents and no weeds) each of 0.25 ha in transplanted rice. Weeds were managed with hand weeding in the wet season, and hand weeding and herbicides in the dry season. Plastic fences were installed to exclude rodents. We examined the weed cover and relative abundance of weed species, rodent damage, rodent population dynamics and rice yield loss caused by rodents and weeds. The dominant rodent species was Bandicota bengalensis. In the dry season, Cyperus difformis was dominant at the tillering stage and Echinochloa crus‐galli was the dominant weed species at the booting stage. In the wet season E. crus‐galli was a dominant weed throughout the season. Damage by rodents was higher in the dry season. There were larger economic benefits for best weed management and effective rodent control in the dry season (258 US$/ha) than in the wet season (30 US$/ha). Concurrent control of weeds in and around rice fields combined with coordinated community trapping of rodents during the early tillering stage and ripening stage of rice are recommended management options.